Extensive pleomorphic adenoma of parapharyngeal space with pterygopalatine fossa and skull base penetration – case report - Gierek, Tatiana; Paluch, Jarosław; Markowski, Jarosław; Zralek, Czesław; Kajor, Maciej; Jura-Szołtys, Edyta; Witkowska, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2010)
The authors present a very rare case of a giant pleomorphic adenoma arising from the parapharyngeal space with penetration to the pterygopalatine fossa and skull base in a 62-year old patient. The authors put emphasis on diagnostic and surgical treatment of tumours in this anatomical region. It is necessary for surgical treatment of tumours in this area to be carried out by a multi-specialty laryngological-neurosurgical team, having long-term experience in skull base surgery.